2022
DOI: 10.3389/fpubh.2022.918658
|View full text |Cite
|
Sign up to set email alerts
|

Calves as Main Reservoir of Antibiotic Resistance Genes in Dairy Farms

Abstract: A side effect of antibiotic usage is the emergence and dissemination of antibiotic resistance genes (ARGs) within microbial communities. The spread of ARGs among pathogens has emerged as a public health concern. While the distribution of ARGs is documented on a global level, their routes of transmission have not been clarified yet; for example, it is not clear whether and to what extent the emergence of ARGs originates in farms, following the selective pressure exerted by antibiotic usage in animal husbandry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…While tetracycline resistance was relatively common on the farms investigated here, the authors do not believe that oxytetracycline sprays (one treatment of which has previously been estimated to use approximately 3 mL of product per 3 s spray (47), with the entire 150 mL spray can containing 390 mg of oxytetracycline hydrochloride), significantly impacted the likelihood of occurrence of AMR on farm, compared to the systemic use of tetracyclines. A number of other authors have found tetracycline resistance to be relatively common on dairy farms and their environment, even where tetracyclines are not frequently used (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…While tetracycline resistance was relatively common on the farms investigated here, the authors do not believe that oxytetracycline sprays (one treatment of which has previously been estimated to use approximately 3 mL of product per 3 s spray (47), with the entire 150 mL spray can containing 390 mg of oxytetracycline hydrochloride), significantly impacted the likelihood of occurrence of AMR on farm, compared to the systemic use of tetracyclines. A number of other authors have found tetracycline resistance to be relatively common on dairy farms and their environment, even where tetracyclines are not frequently used (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are an effective means of treating/preventing diarrhea in calves. However, in recent years, environmental residues and drug-resistant pathogenic bacteria caused by the abuse of antibiotics have become a common problem in cattle production [ 9 , 10 , 11 , 12 ]. Therefore, many countries and regions have restricted the use of some antibiotics in animals and animal feed, and it is necessary to find new and safe alternatives to antibiotics.…”
Section: Introductionmentioning
confidence: 99%